Financing Asia's Growth - Gemma B. Estrada; Marcus Noland; Donghyun Park; Arief Ramayandi (Asian Development Bank (ADB), 2015)
Recent key challenges highlight the need to revisit Asia's financial development. These include the region's growth slowdown since the global crisis, compounded by a less benign external environment; internal structural challenges, such as population aging; and the maturing of much of the region into middle-income status. The evolving shift in the region's growth paradigm from one based primarily on investment to one based on both investment and productivity growth also underscores the urgency for financial development. For economic growth to benefit more from a sound and efficient financial system, financial development should be complemented with structural and policy reforms in other areas. This means that financial development and inclusion work best in a policy environment that is conducive to growth and development.
hdl:11540/5060
Keywords: E44; G20; G28; 330; economic growth; finance sector; financial development; financial inclusion; productivity